Why it can be wise for smart people to listen to their government sometimes: a painful lesson from the international pattern of COVID-19 death rates - Burhan, Nik Ahmad Sufian; Sabri, Mohamad Fazli; Rindermann, Heiner (Ulster Institute for Social Research, 2024)
The World Happiness Report (WHR) 2021 revealed that public trust in government institutions was helpful in reducing COVID-19 death rates. Societies with higher levels of institutional trust are more likely to follow official orders, leading to greater success of virus suppression strategies implemented by the government. This study adapted an original linear regression model from WHR 2021 to examine the relationship between cognitive ability (CA) and COVID-19 mortality at the cross-country level. Regression analyses revealed that high-CA societies had significantly higher COVID-19 death rates (β = +.48 and +.64, r = +.43). Further regression analyses between CA and institutional variables demonstrated that CA is negatively associated with confidence in the national government (β = -.35 and -.56, r = -.10). CA also correlates negatively with institutional trust (β = -.20 and -.43, r = +.13), although its association with interpersonal trust is positive (r = +.68). To corroborate the negative patterns, correlations between CA and both public and expert perceptions of corruption were examined. Results showed that the negative correlation of CA with expert perception (r = -.70, more intelligent – less corrupt) was twice as strong as with public perception of corruption (r = -.35). Assuming that expert perception is a more reliable measure of corruption prevalence compared to public perception, the results imply that in societies with high CA, the public is under-convinced that their governments are not corrupt. Smarter societies appear to have missed opportunities to further reduce COVID-19 related deaths due to their relatively low level of trust in government and institutions. © 2024 Ulster Institute for Social Research. All rights reserved.